SODOM AND GOMORRAH AND PLATES TECTONIC - Bergoeing, Jean Pierre (Mercator, 2018)
A Geomorphologic-tectonic study is done by the author about the destruction of Sodom and Gomorrah in the Death Sea. This has been a subject of several studies over the centuries. Bible studies that focus on scientific studies today. A geomorphologic approximation is carried out by the author determining the tectonic reasons that causes the destruction and disappearance of these cities. Keywords : Tectonics, Sliding faults, Paleo-weather.